ERECTOR SPINAE PLANE BLOCK AS A RESCUE THERAPY IN CHRONIC POSTHERPETIC NEURALGIA: A CASE REPORT - Anto, Lie; Ismi A. Hamdani; Irma Savitri; Tiara Aninditha; Nurul Fadli; Yusak Mangara Tua Siahaan; Dyah Tunjungsari; Henry Riyanto Sofyan (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Postherpetic Neuralgia (PHN) is a persistent neuropathic pain following Herpes Zoster, particularly in the elderly. A case is reported of a 70-year-old man with PHN two months after HZ, experiencing burning and throbbing pain in the right T11–12 thoracic dermatomes with a pain scale of 8/10, paroxysmal in nature up to 10 times/day, triggered by touch, and disturbing sleep. The pain was unresponsive to gabapentin 1,800 mg/day and amitriptyline 12.5 mg/day. Two perineural injections of 5% dextrose reduced the pain to 6/10. At week 13, an ultrasound-guided erector spinae plane block was performed at the T12 level using 2% lidocaine (10 mL) and dexamethasone 5 mg, which rapidly reduced the pain from 6/10 to 0/10, with sustained improvement and discontinuation of medication. No complications were found. This case shows the erector spinae plane block as a safe, minimally invasive, and effective rescue therapy for refractory PHN.